European Stop Tyrosine Kinase Inhibitor trial (EURO-SKI) in chronic myeloid leukemia: Final analysis and novel prognostic factors for treatment-free remission - Mahon, François-Xavier; Pfirrmann, Markus; Dulucq, Stéphanie; Hochhaus, Andreas; Panayiotidis, Panayiotis; Almeida, Antonio; Mayer, Jiri; Hjorth-Hansen, Henrik; Janssen, Jeroen J.W.M.; Mustjoki, Satu; Martinez-Lopez, Joaquin; Vestergaard, Hanne; et al. (Journal of clinical oncology, 2024)
Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. - The European Stop Kinase Inhibitors (EURO-SKI) study is the largest clinical trial for investigating the cessation of tyrosine kinase inhibitors (TKIs) in patients with chronic myeloid leukemia in stable deep molecular remission (DMR). Among 728 patients, 434 patients (61%; 95% CI, 57 to 64) remained in major molecular response (MMR) at 6 months and 309 patients of 678 (46%; 95% CI, 42 to 49) at 36 months. Duration of TKI treatment and DMR before TKI stop were confirmed as significant factors for the prediction of MMR loss at 6 months. In addition, the type of BCR::ABL1 transcript was identified as a prognostic factor. For late MMR losses after 6 months, TKI treatment duration, percentage of blasts in peripheral blood, and platelet count at diagnosis were significant factors in multivariate analysis. For the entire study period of 36 months, multiple logistic regression models confirmed duration of treatment, blasts, and transcript type as independent factors for MMR maintenance. In addition to the duration of treatment, transcript type as well as blasts in peripheral blood at diagnosis should be considered as important factors to predict treatment-free remission.
Online veröffentlicht: 12. März, 2024
Gesehen am 27.01.2025